Low-Temperature Combustion-Synthesized Nickel Oxide Thin Films as Hole-Transport Interlayers for Solution-Processed Optoelectronic Devices - Bai, Sai; Cao, Motao; Jin, Yizheng; Dai, Xinliang; Liang, Xiaoyong; Ye, Zhizhen; Li, Min; Cheng, Jipeng; Xiao, Xuezhang; Wu, Zhongwei; Xia, Zhouhui; Sun, Baoquan; et al. (Advanced energy materials, 2014)
A method to deposit NiOx thin films by employing combustion reactions is reported and a low processing temperature of 175 °C is demonstrated. The resulting NiOx films exhibit high work functions, excellent optical transparency, and flat surface features. The NiOx thin films are employed as hole‐transport interlayers in organic solar cells and polymer light‐emitting diodes, exhibiting superior electrical properties.